1984
DOI: 10.1139/p84-156
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal contributions to the vacuum polarization in the't Hooft–Veltman gauge

Abstract: The Ward–Takahashi–Slavnov–Taylor (WTST) identities are examined in the 't Hooft–Veltman gauge ∂∙A + λA2 = 0. It is found that gauge invariance implies that there is a contribution to the longitudinal part of the vacuum polarization that is proportional to λ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This extends the one loop calculations of [17,18]. Whilst the authors of [17,18] were the first to observe that the longitudinal part of the photon is renormalized unlike in a linear gauge, we have carried out a slightly more general analysis by allowing for a covariant gauge parameter α and the inclusion of an additional coupling ξ in order to track the loop calculation in a similar way to the usual coupling constant a. The coupling ξ was not initially fixed to a specific value.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This extends the one loop calculations of [17,18]. Whilst the authors of [17,18] were the first to observe that the longitudinal part of the photon is renormalized unlike in a linear gauge, we have carried out a slightly more general analysis by allowing for a covariant gauge parameter α and the inclusion of an additional coupling ξ in order to track the loop calculation in a similar way to the usual coupling constant a. The coupling ξ was not initially fixed to a specific value.…”
Section: Discussionmentioning
confidence: 82%
“…As the latter do not appear in linear covariant gauges in QED, the 't Hooft-Veltman gauge clearly could be used as a laboratory to study simple issues related to gauge field self-interaction. Indeed in [17,18] a one loop calculation showed that the corresponding covariant gauge fixing parameter was renormalized. Therefore, in light of these observations it is the purpose of this article to record the full three loop renormalization of QED in the 't Hooft-Veltman gauge.…”
Section: Introductionmentioning
confidence: 99%
“…Preregularization permits freedom in the parameterization of infinity and even (as in the above example) allows one to avoid such parameterizations entirely. In the above example the limit A + 0 is taken prior to computing the divergent integrals to ensure that n,, is transverse; indeed if A # 0, the Ward identities imply that there is a longitudinal component of It,, (26). We thus see that the 't Hooft-Veltman gauge can be used to generate an additional shift parameter that can absorb quadratically divergent photon mass terms to recover "transversality.…”
Section: Fig 8 Vacuum Polarization In Scalar Qedmentioning
confidence: 94%